Bitcoin and the rise of decentralized autonomous organizations - Ying-Ying Hsieh; Jean-Philippe Vergne; Philip Anderson; Karim R. Lakhani; Markus Reitzig (Journal of Organization Design, 2018)
Bitcoin represents the first real-world implementation of a "decentralized autonomous organization" (DAO) and offers a new paradigm for organization design. Imagine working for a global business organization whose routine tasks are powered by a software protocol instead of being governed by managers and employees. Task assignments and rewards are randomized by the algorithm. Information is not channeled through a hierarchy but recorded transparently and securely on an immutable public ledger called "blockchain." Further, the organization decides on design and strategy changes through a democratic voting process involving a previously unseen class of stakeholders called "miners." Agreements need to be reached at the organizational level for any proposed protocol changes to be approved and activated. How do DAOs solve the universal problem of organizing with such novel solutions? What are the implications? We use Bitcoin as an example to shed light on how a DAO works in the cryptocurrency industry, where it provides a peer-to-peer, decentralized, and disintermediated payment system that can compete against traditional financial institutions. We also invited commentaries from renowned organization scholars to share their views on this intriguing phenomenon.
Keywords: 650; Decentralized autonomous organization; Blockchain; Consensus mechanisms; New forms of organizing; Organizational forms